Constraints to sustainable energy technology implementation: Insights from an emerging economy using ISM-MICMAC analysis - Zhengguang Shi; Bingyao Li; Raluca Simina Bilti (PLoS ONE, 2025)
The growing environmental, economic, and social challenges have compelled governments and policymakers to incorporate sustainable energy technologies. However, the development of sustainable energy technologies is hindered by various barriers in emerging economies like China. Although, previous studies attempted to investigate these barriers but there is dearth of studies determining the hierarchy ranking of the barriers. ISM based approach has been developed to fill this research gap by presenting the barriers on the basis of importance level. Through literature survey, fourteen barriers have been identified which were confirmed from expert’s panel. These fourteen barriers are displayed in six layers of ISM hierarchy form from bottom to top which exhibits their ranking on priority base. Findings revealed that high initial cost, longer payback period, and lack of proper financing facilities are major barriers in adopting sustainable energy technologies. However, lack of social acceptance is the least important barrier in sustainable energy technologies. This work will assist companies to better understand the relationships between the barriers which is useful to reduce the barriers strength by implementing effective strategies.